Spatio temporal distribution of forest fire using landsat [NDVI] and [NBR] / Mohammad Daniel Wafry Mohd Nazari - Mohammad Daniel, Mohammad Daniel Wafry (2019)
Forest fire are common problem in world where it is the main factor of climax change according to the HAL archive - ouvertes, the causes of forest fires are varied and their distribution differs among countries, but may also differ spatially and temporally within the same country and mostly it is cause by human other than that forest fire are effected by the natural causes. The first effect of forest fire is destroyed homes, wildlife as well as the vegetation, the soil in the area will be completely destroy and the forest growth are effected. The large amount of smoke release to the air can also cause an air pollution. The forest fire study in Malaysia are not much compare to other country. Chuping are the northern area in Perlis which is happen to be the hottest area in Malaysia yearly the forest was burned and the area effected are been studied yet. most researcher study about the forest fire are focusing on vegetation index and the land surface temperature. Normalized Burn ratio (NBR) can provide us the information about the area of bum severity area as confirmation that the area was bumed. The aim of this research is to determine Spatio temporal distribution of forest fire episode between 2013 - 2016 at Chuping Perlis based on Normalized Difference Vegetation Index (NDVI) and Normalized Bum Ratio (NBR) of Landsat images at Chuping Perlis. The objective of the study to generate the vegetation and bum severity indices coverage based on NDVI and NBR. And the second objective to estimate the change of NDVI and NBR, and the third are to determine the spatio temporal distribution of forest fire based on NDVI and NBR change. The study attempts to provide a comprehensive review of current research with respect to remotely sensed data and methods used to model post-fire effects and forest recovery pattems in the forest regions. As a result, the change of area of vegetation can be identify in five different classes. To support the vegetation value effect of forest fire the bum severity ratio was used to view the area of fire happen to make sure the relation of forest fire with the vegetation index. The conclusion of this study the correlation between NDVI and NBR were proved and the significant of the study achieve the aim of the study were the area of forest fire can be monitor using the both method.